Comparison of Rahn Contract from the Perspective of Islamic Law and Indonesian Guarantee Law - Aang Asari; Muhammad Irkham Firdaus (Journal of Islamic Economics Lariba, 2022)
This paper analyzed pawn in comparison between the Civil Code and Islamic law. It examined the specific differences between pawn contracts in Islamic law and Indonesian positive law to compare two contract theories. The method used in this paper is a qualitative approach. The type used in writing this article is library research. The author examines, observes and looks for data from reference books that can be accounted for. The result of the research in this paper is that the term pawn in Islamic law is called ar-rahn. The difference between rahn and pawn in positive law, among others, is regarding the maintenance of the collateral. In Islamic law the pawnbroker is not subject to the term interest or additional costs outside the pawn agreement, but there is only an additional maintenance fee for the collateral. Whereas in positive law, in addition to the cost of maintaining goods, there is also an additional cost called 'interest' that must be borne by the lender. In Islamic law collateral goods are not limited to movable goods, but also immovable goods, while in positive law the collateral object is only limited to movable goods.